"This Mecca for the Pilgrims of Pleasure": tourism, modernity, and Victorian London, 1840-1900 - De Sapio, J; Joseph De Sapio (2011)
This dissertation argues that during the nineteenth century, the journey to London revealed a world undergoing systemic change as industrialisation steadily eroded the traditional rhythms of the countryside in favour of urban modernity; indeed, London is regarded as a synecdoche for the forces shaping the wider world. This work uses tourist narratives to London as investigative tools to examine the ways in which individuals comprehend the modern changes occurring around them, as represented by the British capital, and does so in a comparative fashion, investigating the British Empire, the United States, Britain itself, and continental Europe. In so doing, it addresses two questions: first, whether one’s acceptance or rejection of modernity was predicated upon specific social and national preconditions; and second, whether the idea of nineteenth-century modernity was itself a non-universal construction dependent upon a variety of socio-cultural outlooks. The evidence for this study is drawn from the published and unpublished narratives of tourists from the four different contexts mentioned above, and divided into four chapters to focus upon each group. This study is grounded in a theoretical context which establishes a correlation between the methods used to interpret the city’s spaces, and the methods used to interpret modernity more generally. I conclude that the changes occurring from the interaction between global modernity and local culture were regarded with ambivalence and uncertainty, judgments influenced by London’s impact on the visitors mentioned above. The city gives a physical dimension to the travellers’ imagined fears, benefits, or concerns over future progress. Victorian London is thus one focus for a transformation affecting large segments of the nineteenth-century world, illustrating that modern industrial changes were ultimately perceived as being ambiguous and ambivalent forces.